Comparative study on regeneration of spent activated carbon by chemical and thermal treatments - Fadzlie Bin Fauzi (School of Environmental Engineering University Malaysia Perlis, 2011)
Spent activated carbon had been collected from industry for regeneration purpose. Ussually carbon that been used in industrial for treatment purpose will disposed as it include in schedule waste. Regeneration of activated carbon can be done by thermal treatments and chemical package treatments. The objective in this study to evaluate the performance of spent activated carbon after regeneration by chemical and thermal treatments. Two methods of regeneration had been used for this study which is chemical regeneration and thermal.